Early intestinal microbiota changes in aged and adult mice with sepsis - Yuan, Yangyang; Liu, Shaohua; Ding, Xianfei; Li, Ying; Zhang, Xiaojuan; Song, Heng; Qi, Xueyan; Zhang, Zihao; Guo, Kaiyuan; Sun, Tongwen (Frontiers in Cellular and Infection Microbiology, 2022)
Background The mortality rate associated with sepsis in elderly individuals is higher than that in younger individuals. The intestinal microbiota has been demonstrated to play an important role in the occurrence and development of sepsis. The purpose of this study was to investigate the differences in the intestinal microbiota between aged and adult mice with sepsis. Methods Thirty male C57BL mice were randomly divided into two groups: 15 in the adult group (AD group) and 15 in the age group (Age group). All the mice underwent caecal ligation and puncture to induce sepsis. Mice faeces were collected, and analysed using 16S rRNA sequencing. The liver and colon tissues were collected. Results There were significant differences in intestinal microbiota composition between the two groups. Compared with adult sepsis mice, the diversity of intestinal microbiota in the aged group was significantly reduced and the structure of dominant intestinal microbiota was changed. In the Age group, the microbiota associated with inflammatory factors increased, and the microbiota associated with the production of SCFAs (Ruminiclostridium, Prevotellaceae_UCG-001, Rikenella, Parabacteroides, Oscillibacter, Odoribacter, Muribaculum, Lachnoclostridium, Intestinimonas, Faecalibaculum, Anaerotruncus, Alloprevotella and Absiella) decreased. The metabolic pathways related to the microbiota also changed. Moreover, the proportion of inflammatory factors in Age group was higher than that in AD group. Conclusion Our results showed that there were significant differences in the abundance and structure of microbiota between aged and adult sepsis mice, Aged sepsis mice have more severe intestinal microbiota destruction and liver tissue inflammation than adult sepsis mice.